Bullous pemphigoid in 65 years old female: a case report - Sanjaya, I Dewa Made Rendy; Artana, Putu; Hari, Embun Dini (Bali Dermatology and Venereology Journal, 2018)
Introduction: Bullous pemphigoid is an autoimmune disorder. The incidence of bullous pemphigoid has increased over time, current understanding regarding treatment and complication is an important issue considering the disease often occur in elderly resulting in high rates of morbidity to the patients. Aim of current case report is to describe the clinical relevance regarding symptom and treatment of bullous pemphigoid.Case presentation: A 65 years old female patient, came with chief complaints of bullae in abdominal region with itching and burning sensation in the ruptured bullae. Over time bullae spread in lower and upper extremity. Patient was admitted for four days with therapy intravenous steroids, oral antihistamine, and potent topical steroids. Patient was discharged from hospital in well condition.Conclusion: Bullous pemphigoid is an inflammatory autoimmune skin disease and usually result in good prognosis with adequate management.Keywords: autoimmune, bullous, pemphigoid, skin, disease.Ã‚Â